Features of software implementing the prefix search method in cryptographically protected databases - Lilikovych, Serhii; Yesin, Vitalii (Computer Science and Cybersecurity, 2023)
The article addresses the specific considerations associated with the development of software implementing the prefix search method in cryptographically protected databases. This method is a variant of symmetric searchable encryption, which allows search among the encrypted data. The prefix search method allows searching for prefixes among encrypted data without the need for decryption. Such an approach resolves the issue of maintaining data confidentiality stored on remote or cloud servers. However, its usage introduces a set of issues that must be considered during the development of the corresponding software. The paper analyzes the requirements for software that implements the prefix search method, defines the software architecture, and justifies the choice of technologies and tools for software implementation, including ASP.NET, Java, JavaScript, PHP, Python programming languages, MongoDB database management system, and the FastAPI framework. A description of the deployment process of the corresponding software is provided. To assess the performance of the developed software, the well-known Apache JMeter tool for conducting load testing was utilized. The obtained performance evaluations of the proposed solution indicate acceptable time delays in processing relevant data search queries.